(untitled) (Journal of Geography, Meteorology and Environment, 2021)
This study examined the extent of forest loss and degradation between 1972 and 2018 in Ndokwawest LGA, Delta State, Nigeria. Landsat multispectral images of 1972, 1987, 2002, 2004, 2014 and 2018 were employed for the study. Image classifications were done using ArcGIS 10.5 and four major classes were identified, namely: forest, settlement, bareground and waterbodies. NDVI values of the images were also calculated using ArcGIS 10.5, while additional NDVI data of the study area were obtained from FORTH Remote Sensing Lab. Data were analysed using charts, time series graphs and multiple regression analysis to determine the extent of change in forest canopy cover and forest health. The protective function of the forests was also observed while examining the change in land surface temperature through the years under study. Results showed that much of the forest cover were lost; about 904km2 of forest between 1972 and 2018, mainly from changes to settlements and bare ground. Time series graph showed a decline in the NDVI from 1972 to 2018; an indication of decline in forest health. Significant relationship between forest loss and Land Surface Temperature (LST) with R²= 0.729 was established and the declining NDVI values of the study area was seen to correspond with increasing LST values through the study years. This is an indication of a loss in the protective function of the forests in the study area. NDVI and LST results revealed that the forest zone experienced fragmentation, decline in forest health and protective function within the study period. The study recommended forest conservation and management across the zone and advocated that both the government, stakeholders and individuals contributes to actualizing the target and in turn reduces environmental change impacts in the region.